Mechanistic and Thermodynamic Evaluation of Molnupiravir Binding to Bovine Serum Albumin Using Fluorescence Spectroscopy and In Silico Analysis (Dhaka University Journal of Pharmaceutical Sciences, 2026)
Protein binding regulates a drug's pharmacokinetics, bioavailability, and therapeutic efficacy. This study explores the interaction between the antiviral drug Molnupiravir and bovine serum albumin (BSA), 76% of whose sequence is homologous to human serum albumin and widely accepted in preliminary drug–protein interaction studies, to determine binding mechanisms and pharmacokinetic effects. Fluorescence spectroscopy at physiological pH (7.4) and temperatures (302 and 310 K, representing normal and febrile physiological conditions, respectively) showed concentration-dependent quenching at excitation wavelengths of 280 and 293 nm, indicating the involvement of tryptophan and tyrosine residues in the binding interaction. The Stern-Volmer analysis affirmed a dynamic quenching operation, with constants increasing from 0.0166 to 0.0176 μM⁻¹. Thermodynamic parameters indicate spontaneous, entropy-driven binding (ΔG = −24.4 kJ/mol at 302 K), dominated by hydrophobic interactions. Using AutoDock Vina, binding at Sudlow site I was discovered with an affinity of -7.9 kcal/mol, involving critical residues GLY327 and ARG208.Dhaka Univ. J. Pharm. Sci. 25(1): 65-74, 2026 (June)